An Analysis of Students’ Speaking Ability in Performing as Hotel Receptionist at Phase E Hospitality Department in SMK Negeri 6 Padang - Tama Mutia Anisya; Feby Meuthia Yusuf; Yessy Marzona (JURNAL ARMADA PENDIDIKAN, 2026)
The research was to find out the students’ ability and students difficulties in performing hotel receptionist. This research was conducted at phase E Hospitality Department in SMK Negeri 6 Padang, the academic year 2023/2024. The students had three problems, there were lack of pronunciation, lack of grammar, and lack vocabulary. Based on those problems, the researcher analyzed students’ speaking ability in performing as hotel receptionist at Phase E Hospitality Department in SMK Negeri 6 Padang. The method of the research used is descriptive research. The population was 108 students from 3 classes, which are X PH 1, X PH 2, and X PH 3. In this case, X PH 3 was chosen as the research sample that consists of 36 students and the researcher used a sample random sampling technique. The research instrument used was a speaking test. In data collection technique the opportunity to perform as hotel receptionist in front of the class, while the data analysis technique is carried out by using speaking indicators. Based on the result to speaking test the researcher found that of the 28 of 36 are students present during the research process because 8 are students permission for its own reasons was and the researcher to find that the average of students has a moderate speaking ability indication of 60% in class X PH 3. Through these result find students difficulties in speaking, they are miss pronunciation, mastering grammar, and vocabulary. The researcher concluded the students speaking ability in performing as hotel receptionist was moderate.